Post-fault voltage limit assessment for six-phase induction machines: a synchronous and slip frequency approach - Muhammad Zin, Nooradzianie; Wan Abdul Munim, Wan Noraishah; Abidin, Ahmad Farid; Che, Hang Seng; Mohamad Elias, Mohamad Fathi; Baharom, Rahimi (Institute of Advanced Engineering and Science, 2025)
Six-phase machine research has attracted a lot of attention lately, as seen by the large number of articles and case studies that have been written about it. Six-phase induction machines are prevalent due to their simplicity in construction. A fault-tolerance system is essential to guaranteeing machine operation that is both available and continuous in the event of a disruption or failure in the system. The operational topologies of dual three-phase (D3-IM) and symmetrical six-phase (S6-IM) induction machines were studied in this research. One open-phase fault (1OPF) is covered in the study, and different scenarios including the derating factor, neutral configuration, and maximum torque (MT) operational strategy are taken into account. Using MATLAB software, machine characteristics, machine equations, and Clarke's transformation show the fault-tolerant capability of each type of machine. Moreover, a MATLAB program is developed to assess post-fault voltage control limits, allowing for a comparison between current and voltage control limits. Simulated graph results depicting line-to-line voltages against synchronous and slip frequencies across all possible fault scenarios reveal distinct fault-tolerant capabilities between the two machine types. The comparative study shows that S6-IM offers better fault-tolerant capability than D3-IM based on both various synchronous and slip frequency approaches.